Non-conventional compounds with potential therapeutic effects against Alzheimer's disease - de Castro, Alexandre A; Soares, Flávia V; Pereira, Ander F; Polisel, Daniel A; Caetano, Melissa S; Leal, Daniel H S; da Cunha, Elaine F F; Nepovimova, Eugenie; Kuca, Kamil; Ramalho, Teodorico C (Expert review of neurotherapeutics, 2019)
Alzheimer's disease (AD) is the most common cause of dementia. Clinical progress in this pathogenesis field has drawn the attention of researchers, stimulating the investigation of novel treatment methods. Current therapies that deal with cholinesterase inhibitors and/or NMDA antagonists have shown a modest symptomatic potential, increasing the need for research into more efficient therapeutics. The goal of this review is to summarize the advances in, and the potential of, non-conventional therapies in AD treatment. Areas covered: In this review, the authors describe the current status of unusual therapies in AD treatment, evaluating the modern scientific contexts in which these therapies have been developed. The authors also highlight the usage of methylene blue, natural products, organophosphorus compounds, and Chinese medicine, along with the employment of nanotechnology. Expert opinion: The potential therapies discussed in this review will play increasingly important roles in the prevention and treatment of AD, improving disease management and quality of life for AD patients. Given the annual increasing number of people with dementia, it is crucial to invest in the search for novel therapeutics. In addition, more sophisticated diagnosis techniques are also essential, to allow for an early diagnosis and treatment.
Keywords: Organophosphorus Compounds; neurodegeneration; tradiční čínská medicína; Enzyme Inhibitors; lidé; acetylcholinesterase; natural products; Medicine, Chinese Traditional; organofosforové sloučeniny; nanotechnology; Humans; Methylene Blue; Alzheimer’s disease; Alzheimer Disease; inhibitory enzymů; methylenová modř; Alzheimerova nemoc; Nanotechnology; nanotechnologie; organophosphorus compounds; amyloid-β peptide; methylene blue